(untitled) (Damu Journal of Sport Sciences, 2024)
The research aims to identify the effect of competitive compound training using the two methods (weights and plyometric) on some physical abilities on the one hand and its effect on the momentum at the moment of rising to shoot on the other hand for handball players aged (17-19) years by developing a training curriculum that contains compound exercises using plyometric weights in one performance of the same exercise. Therefore, the researcher used the experimental method with a single-group design with a pre- and post-test. The research sample was represented by Diyala Club players aged (17-19) years participating in the Iraqi League for this age group for the sports season (2022-2023). The research sample was represented by Diyala Club handball players, numbering (10) players, who represent the experimental group. The implementation of the training curriculum took 8 weeks, with 3 training doses per week and a total number of training doses of 24 training doses, and the location of the exercises was in the main part of the training unit. The researcher used the interval training method in its two types, the repetitive and the interval training method, with a training intensity ranging between 75-95% of the players’ capacity, taking into account the fluctuation in the training load. The researcher concluded that this type of training has yielded results in terms of developing the research variables significantly, and this was confirmed by the test results. Therefore, the researcher recommended that trainers should pay attention to this type of training used in the research and include it in their training curricula to benefit from it, in addition to using other types of complex training (qualitative and general).